2021
DOI: 10.1136/bmjopen-2021-053814
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and cannabidiol use among autistic and non-autistic adults in the UK: a propensity score-matched analysis

Abstract: ObjectivesTo assess whether autistic and non-autistic adults differ in their cannabis and cannabidiol (CBD) use, their perceptions of cannabinoid products and their cannabinoid-related support-seeking behaviours.DesignCross-sectional survey.ParticipantsRespondents to an online survey, who self-reported an autism-spectrum disorder diagnosis (autistic participants) or no issues relating to autism (controls). Exclusion criteria were: related/subclinical issues relating to autism, non-UK residence, under 16 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Social stigma associated with the use of CBD and potential judgement of HCPs were barriers to CBD use reported by members of the public which were also concerns reported in other studies 15,16,32,33 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Social stigma associated with the use of CBD and potential judgement of HCPs were barriers to CBD use reported by members of the public which were also concerns reported in other studies 15,16,32,33 .…”
Section: Discussionmentioning
confidence: 53%
“…Caregivers suggested that CBD should not be available over the counter but should be regulated by the government and labelled as a medicine 15 . The concern of being judged or misunderstood for using cannabis was reported as a barrier to CBD use 16 . Leszko and Meenrajan (2021) demonstrated the need for awareness about the difference between CBD and Medicinal Cannabis (MC) as the general public often confuse CBD with MC 15 .…”
Section: Introductionmentioning
confidence: 99%